Pengaruh Warna Kerabang Dan Lama Penyimpanan Pada Suhu Beebeda Terhadap Kualitas Suhu Konsumsi - Yurliasni Yurliasni; Herawati Latif (Agricultural Faculty, 2007)
ABSTRACT.The objective of this research is to learn the effect of shell color and storage length on egg quality. The research was held at the Animal Nutrion Laboratory Departement of Agriculture, Syiah Kuala University. The treatments were shell color 30 SC (dark brown): 30-40 SC (white) with 10 replication and store in 270C and 100C for 35 days. The observation was taken every 7 days. Parameters measured were foam ability and Haugh Unit by group random sampling design with factorial pattern. The result shows that temperature and storage length significantly effect foam ability but not in haugh unit. Storage temperature and storage temperature at 100C show that foam ability is better with the average of 422.31 cm3. Compared to 270C with the average of 394.04 cm3. On the other hand shell color has no effect both on foam ability and Haugh Unit. In general, shell color, storage length and storage temperature have no effect on egg quality.